Victoria Ocampo and Alfonso Reyes: Ulysses's Malady - Doris Meyer (Studies in 20th & 21st Century Literature, 2000)
Ocampo (Argentina, 1890-1979) and Reyes (Mexico, 1889-1959) were arguably Latin America's most influential writers and cultural catalysts in the first half of the twentieth century. They met in Argentina in 1927 and their friendship and correspondence lasted until Reyes's death. Over three decades of private and public discourse, they articulated a similar vision of Latin American identity and its future potential. Because they were both internationally known—Ocampo as founder and director of the literary review SUR, and Reyes as a diplomat and intellectual leader—their ideas found resonance in the Americas and Europe. Two dramatic works they wrote before meeting, Ifigenia cruel (Reyes) and La laguna de los nenúfares (Ocampo), prefigure their approach to the Latin American condition through the themes of displacement and self-renovation. Ocampo and Reyes believed that it would be the task of an educated elite to lead Latin America toward a transnational cultural synthesis and renewal. Ulysses's malady was their metaphor for the postcolonial condition that enabled Latin American minds to be open to exploration and dialogue in search of an authentic identity.
Keywords: Ocampo; Argentine literature; Reyes; Mexican literature; Latin American identity; identity; Ifigenia cruel; La laguna de los nenúfares; displacement; self-renovation; transnational; transnationalism